Development And Validation Of Stability Indicating Uv Spectrophotometric Method For The Estimation Of Atomoxetine Hydrochloride In Bulk And Tablet Dosage Form - PARAG PATHADE; AMOL PAWAR; ABHIJIT GAIKWAD; ASHWINI PANHALKAR (International Journal of Pharma and Bio Sciences, 2011)
A simple, sensitive, accurate, precise, reproducible and cost effective stability indicating UV spectrophotometric method has been developed for quantitative determination of Atomoxetine hydrochloride in bulk and pharmaceutical formulations. The UV spectrum was scanned between 200 to 400 nm and 270.5 nm was selected as maximum wavelength for absorption. Beer’s law was obeyed in the concentration range of 10-80 ïg/ml. Good accuracy (100.18-100.26%), precision (%RSD 0.997-0.995) were found, the method was successfully applied to the pharmaceutical dosage form containing the above-mentioned drug without any interference by the excipients. Results of the analysis were validated as per ICH guidelines. Forced degradation studies includes the effect of temperature, oxidation, photolysis and susceptibility to hydrolysis across a wide range of pH values, were carried out according to the ICH requirements which can be used for the routine and quality control analysis of Atomoxetine hydrochloride in raw material and pharmaceutical formulations.